2018
DOI: 10.1002/soej.12255
|View full text |Cite
|
Sign up to set email alerts
|

Ride‐Sharing, Fatal Crashes, and Crime

Abstract: The advent of smart‐phone based, ride‐sharing applications has revolutionized the vehicle for hire market. Advocates point to the ease of use, lower prices, and shorter wait times compared to hailing a taxi or prearranging limousine service. Others argue that proper government oversight is necessary to protect ride‐share passengers from driver error or vehicle parts failures and violence from unlicensed strangers. Using U.S. county‐level data from 2007 through 2015, we investigate whether the introduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 32 publications
1
58
1
Order By: Relevance
“…Using Uber's individual-level data and its unique surge pricing, Cohen et al (2016) estimate that UberX created $6.8 billion of consumer surplus in 2015. The indirect effects are less clear: recent evidence shows that Uber could benefit public health by reducing drunk driving accidents and fatalities (Greenwood and Wattal 2017;Peck 2017;Dills and Mulholland 2016), though other work finds that it has not affected traffic fatalities in any way (Brazil and Kirk 2016). However, an important part of understanding the future of Uber and similar services involves measuring its effect on other modes of transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Using Uber's individual-level data and its unique surge pricing, Cohen et al (2016) estimate that UberX created $6.8 billion of consumer surplus in 2015. The indirect effects are less clear: recent evidence shows that Uber could benefit public health by reducing drunk driving accidents and fatalities (Greenwood and Wattal 2017;Peck 2017;Dills and Mulholland 2016), though other work finds that it has not affected traffic fatalities in any way (Brazil and Kirk 2016). However, an important part of understanding the future of Uber and similar services involves measuring its effect on other modes of transportation.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review suggested that designated driver programmes were not found to be effective in decreasing alcohol-related traffic outcomes. 9 Research has also assessed the effects of network ridesharing on accidents, [10][11][12][13][14][15][16] with six studies [10][11][12][13][14][15] looking at the association between network ridesharing and alcohol-impaired driving in the United States (US). Results are mixed, with Martin-Buck, 12 Greenwood and Wattal, 13 Peck 14 and Morrison et al 15 showing reductions in alcoholrelated crashes after Uber was introduced, whereas Brazil and Kirk 10 and Dills and Mulholland 11 did not observe any change in these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The driving history or criminal background of ridesharing drivers is not always carefully checked by platform companies [9,10]. In this context, there are many potential safety risks for ridesharing passengers [11,12].…”
Section: Introductionmentioning
confidence: 99%